RESISTENSI PETANI : SUATU TINJAUAN TEORITIS - Oetami Dewi (Sosio Informa, 2007)
If we are talking about the resistance, we can’t avoid talking and discussing about thepeasant, because the concept for resistance actually came from the peasant. Briefly in this paper I would like to convey that if we want to know deeply about the resistance we should now first about the history and concept for building the theory. In this paper, try to make many differences and understanding meaning from many references that talking about resistance relating to the peasant. That resistance can be divided into many meaning, and the main resistances are active and passive resistance. For passive the characteristics are different than in active resistance by the appearance from the kind of how the peasant react to what they think it could be different from what they want to. But for active resistance the appearance more destructive than in passive, since their willingness never gives more attention until they can’t stand up anymore. The form of resistance also many kinds relating to the situation, condition and the culture form the communities.Keyword : resistance, the peasant